Rethinking Regenerative Medicine From a Transplant Perspective (and Vice Versa). Issue 2 (February 2019) - Orlando, Giuseppe; Murphy, Sean V.; Bussolati, Benedetta; Clancy, Marc; Cravedi, Paolo; Migliaccio, Giovanni; Murray, Patricia
Abstract : Abstract: No field in health sciences has more interest than organ transplantation in fostering progress in regenerative medicine (RM) because the future of no other field more than the future of organ transplantation will be forged by progress occurring in RM. In fact, the most urgent needs of modern transplant medicine, namely, more organs to satisfy the skyrocketing demand and immunosuppression-free transplantation, cannot be met in full with current technologies and are at risk of remaining elusive goals. Instead, in the past few decades, groundbreaking progress in RM is suggesting a different approach to the problem. New, RM-inspired technologies among which decellularization, 3-dimensional printing and interspecies blastocyst complementation, promise organoids manufactured from the patients' own cells and bear potential to render the use of currently used allografts obsolete. Transplantation, a field that has traditionally been immunology-based, is therefore destined to become a RM-based discipline. However, the contours of RM remain unclear, mainly due to the lack of a universally accepted definition, the lack of clarity of its potential modalities of application and the unjustified and misleading hype that often follows the reports of clinical application of RM technologies. All this generates excessive and unmet expectations and an erroneous perception of what RM really is and can offer. In this article, we will (1) discuss these aspects of RM and transplant medicine, (2) propose a definition of RM, and (3) illustrate the state of the art of the most promising RM-based technologies of transplant interest. Abstract : Regenerative medicine (RM) aims to replace, regenerate, or repair tissues or organs. RM has enormous clinical potential but also faces important obstacles like the ex vivo or in vivo regeneration of tissues and organs (with techniques such as decellularization, 3D printing, stem cells, organoids, and blastocyst complementation) but also ischemia reperfusion and immune and inflammatory -mediated reactions (regenerative immunology).